Collaborative Governance on Ecotourism: Towards Sustainable Tourism Development - Sri Mulyani; Retno Dewi Pramodia Ahsani; Daya Negri Wijaya (Jurnal Borneo Administrator, 2021)
This study analyses collaborative governance in sustainable ecotourism development in Magelang Regency, Central Java province. Strengthening the collaboration of the three actors is needed in developing ecotourism because it comprehensively regulates natural destinations responsible for the sustainability of natural life, economic activity, and community welfare simultaneously. To explain further the fundamental phenomena that occur in sustainable development. The goal is to create a new environmental friendly concept while also improving people's welfare, the economy, and peaceful social activities. Data were collected from in-depth interviews and observations. Interviews were conducted with 8 local government staffs, 22 ecotourism managers, and 42 communities around the destination. Then an analysis was carried out with Nvivo12+ to see the collaboration of sustainable Ecotourism governance in Magelang Regency. Three variables become benchmarks in the study: planning, implementation, and utilization. Each was measured by using six indicators. The study results showed significant local communities and businesses/private involvement in managing and developing ecotourism. Meanwhile, the local government actors need to strengthen their involvement and response in ecotourism development. So far, the response has been relatively slow and waiting for the independent development of destinations that the community has carried out. Therefore, in the future, it is necessary to strengthen collaboration to ensure effective management of natural resources in ecotourism, which can be achieved through the support and cooperation of local government agencies, businesses/private, and the communities.